Assessment of Diabetes-Specific Routine for Adolescents with Type 1 Diabetes Mellitus - Reyam Abass Yasir, Afifa Rida Aziz, (Pakistan Journal of Medical & Health Sciences, 2022)
Aims: to assess diabetes-specific routine for Adolescents with Type 1 Diabetes Mellitus and to find out the relationship between adolescents’ diabetes-specific routine and their sociodemographic characteristics. Methodology: descriptive cross-sectional study design was carried out for the Assessment of Diabetes-Specific Routine for Adolescents with Diabetes Mellitus Type 1 in Diabetes and Endocrinology Center at Al- Nasiriya City from January 9th, to March 23, 2022. The sample consist of (110) adolescents was selected and they were attending Diabetes and Endocrinology Center for treatment and follow-up. The information was gathered through the use of self-administered instruments which are the diabetes-specific routine scale. Results: the adolescents expressed a moderate response regards specific diabetic routine of T1DM at all studied items of the scale except, the items number (1, 2, 3, 4, 16, 17, 18, 19, 20, 22, 23 and 24) the responses were poor as indicated by low mean scores, as well as, the items number (8, 9 and 14) the responses were good as indicated by higher mean scores. Conclusion: (48.2%) of adolescents exhibited that they follow a routine on a moderate level and there is a significant difference between (diabetic-specific routines for adolescents with diabetes mellitus type 1) and some sociodemographic and clinical variables.